Travel Marketing, Tourism Economics and the Airline Product An Introduction to Theory and Practice - Camilleri, Mark Anthony (Tourism, Hospitality & Event Management,, 2018)
This book provides a comprehensive introduction to travel marketing, tourism economics and the airline product. At the same time, it provides an overview on the political, socio-economic, environmental and technological impacts of tourism and its related sectors. This publication covers both theory and practice in an engaging style, that will spark the readers' curiosity. Yet, it presents tourism and airline issues in a concise, yet accessible manner. This will allow prospective tourism practitioners to critically analyze future situations, and to make appropriate decisions in their workplace environments. Moreover, the book prepares undergraduate students and aspiring managers alike with a thorough exposure to the latest industry developments. "Dr. Camilleri provides tourism students and practitioners with a clear and comprehensive picture of the main institutions, operations and activities of the travel industry." Phili p Kotler, S.C. Johnson & Son Distinguished Professor of International Marketing, Kellogg School of Management, Northwestern University, Evanston/Chicago, IL, USA.